Framing Pemberitaan Bullying Binus School Serpong di Media Jurnalistik Online Tirto.Id dan Tempo.Co - Chan, Fikri Azis; Saragih, M. Yoserizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research is based on a case that went viral and became the talk of many people, namely the bullying case experienced by one of the Binus School Serpong students, which in the case of bullying was carried out by Geng Tai, a group containing Binus School Serpong students and one of its members is rumored to include the son of a well-known artist, Vincent Rompies. This incident is still a public conversation, especially through social media X or Twitter. This research seeks to explore how news framing shapes news due to the public's lack of understanding of news texts. Framing analysis is used in descriptive qualitative research by Zhongdang Pan and Gerald M. Kosicki. Framing Analysis of Zhongdang Pan and Gerald M. Kosicki Model on bullying news in journalism is studied in this research. This study examines the Zhongdang Pan and Gerald M. Kosicki Framing Model on bullying news in journalistic media from the perspective of Tirto.id and Tempo.co. Syntactic, script, thematic, and rhetorical indications were found in Tirto.id and Tempo.co in the Zhongdang Pan and Gerald M. Kosicki model. These news articles have no graphics.